Diagnóstico de la producción porcina en los cantones Catamayo y Espíndola de la provincia de Loja - Cobos Torres, Ítalo Geovanny (2014)
In Ecuador swine raising is an important activity among lower-income rural areas, particularly in the province of Loja. To identify the current situation of pig production is projected this research, raising the following objectives: 1. Determine the productive and reproductive parameters of pig through a diagnosis in Catamayo Espindola and cantons; 2. Identify the marketing chain of pig production in Catamayo Espindola and cantons; 3. Prepare a proposal for the improvement of pig production, based on the results of the diagnosis; The work was carried out between November 2012 and June of 2013, formed part of scientific research, and its character of prospective, descriptive, quantitative and qualitative application for some variables. The technique used was the survey of 40 swine production units. The results concluded that: the extensive form is practiced in 60% of farms Espindola, and intensively in 80% Catamayo, the specialty is the fattening farm in Catamayo 100% and 73% of Espindola, the continuous production system applies in 90% of Catamayo and all in-all out in 63% of Espindola. The predominant landrace Espindola 76%, and in 70% Landrace Catamayo; fattening category is the one that stands out most in the 39% Catamayo and 26% Espindola; 90% of facilities are on level ground in Catamayo and Espindola, with sufficient availability of water, electricity and road carrozable. Espindola facilities 80% are brick walls, floor and ceiling of zinc in 80% Catamayo the walls and floor are concrete and tile roof, food and water bowls are on the floor in 100% of farms in Catamayo and in 83% of Espindola. The player starts mounted on Espindola at 12 months, the producers know detect heat, bring to graze and provide vaccinations to pregnant sows, prepare for the birthing bed, move to the sow to the corral with three days in advance; in 40% of castrated Catamayo Espindola and piglets. Fattening time is 2-4 months in 90% of Catamayo and 5-8 months at 63% of Espindola. In 100% of farms Catamayo and Espindola do not keep records, do not have sewage oxidation pond. In 70% of Catamayo the diet is restricted, 60% Espindola is at will, in both cantons balanced provided is purchased. The first mating of gilts occurs at 8-9 months in 100% Catamayo, and Espindola 83% at 10-12 months, the free ride is applied Catamayo 60% and 57% Espindola. In 60% of Espindola is chosen to producers by phenotypic condition and 60% for production traits Catamayo. The production rates are similar in pigs of both cantons vary slightly in weight at the beginning of fattening and carcass, the marketing is similar.